DINÂMICA HIDROLÓGICA DO RIO AQUIDAUANA E SEUS IMPACTOS NA CIDADE DE AQUIDAUANA/MS - Rafael Ribeiro Polvere (2022)
Large floods and floods, as well as other types of natural disasters, are characterized by the large amount of rain in a hydrographic basin and have caused several environmental and socioeconomic damages. They are usually characterized by overflowing water from a river, but they are always linked to relief, use and occupation of the hydrographic basin and even the climate of the region. Depending on the frequency and intensity, these natural phenomena can associate social and environmental damage. The Aquidauana River watershed covers several cities in Mato Grosso do Sul, in which it is verified that the municipalities most affected by periodic floods are in the middle and lower course of the Aquidauana River, and these cities suffer from all the anthropic and natural transformations that occur in the natural environment in the middle and upper course of the basin. The cities of Aquidauana/MS and Anastácio/MS are cities on the banks of this river and that are seasonally affected by the occurrence of floods, causing great disturbances for their population. In this context, the work aims to analyze the flooding processes of the hydrographic basin, through natural and social conditions, characterization of the rainfall that originates and the dynamics of these floods, so that the results of this study can help in minimizing the impacts caused by them and in watershed planning.